Facile synthesis of lanthanum-doped SrTiO3 nanocubes mediated by cetyltrimethylammonium bromide and tert-butylamine under solvothermal condition and their tunable electrical properties - Yulia Eka Putri; Humaira Faradilla; Dedi Satria; Diana Vanda Wellia (Chimica Techno Acta)
The electrical conductivity of low concentrations of lanthanum-doped SrTiO3 nanocube ceramics synthesized using the facile solvothermal method in mixed organic and inorganic solvents with cetyltrimethylammonium bromide (CTAB) as a capping agent and tert-butyl amine (TBA) as a mineralizer was investigated. X-ray diffraction patterns confirmed the formation of a high-purity perovskite phase, corresponding to the standard data and the pattern refinement results. The particles of the sample were nanocubes, whereas the La-doped SrTiO3 sample particles were more uniform in size and shape, as shown in TEM images. The FT-IR spectrum confirmed the vibration of the CH3-N+ groups from CTAB and TBA, indicating an electrostatic interaction between their functional groups and the particle surface. Substitution of La3+ ions at low concentrations increased electrical conductivity compared to the undoped SrTiO3 sample. Lanthanum donates excess electrons, thereby increasing the number of electron carriers, which causes a reduction in the band gap energy according to the UV-DRS spectrum analysis using the Tauc equation.